Comparison of stereotactic body radiation therapy versus surgery for multiple primary lung cancers after prior radical resection: A multicenter retrospective study. (May 2023) - Dong, Baiqiang; Chen, Runzhe; Zhu, Xuan; Wu, Qing; Jin, Jia'nan; Wang, Wenqing; Zhu, Yujia; Jiang, Hui; Bi, Nan; Wang, Xu; Xu, Xiaofang; Xu, Yujin; et al.
Highlights: The appropriate treatment for MPLC patients who aren't suitable for reoperation remains uncertain. We found that SBRT is a safe and effective alternative treatment option for MPLC patients after prior radical resection. Our study provides a reference for clinicians regarding the appropriate treatment for such patients. Abstract: Background: Patients who previously underwent surgical resection of initial primary lung cancer are at a high risk of developing multiple primary lung cancers (MPLCs). The purpose of this study was to compare the efficacy and safety between stereotactic body radiation therapy (SBRT) and surgery for MPLCs patients after prior radical resection for the first lung cancers. Methods: In this multicenter retrospective study, eligible MPLC patients with tumor diameter of 5.0 cm or less at N0M0 who underwent SBRT or reoperation between January 2013 and August 2020 were enrolled. The primary endpoint was the 3-year locoregional recurrence and treatment-related toxicity. Kaplan-Meier method was used to calculate survival rates. The χ 2 test was adapted to assess the difference of categorical variables between the two subgroup patients. Results: A total of 203 (73 in the SBRT group and 130 in the surgery group) patients from three academic cancer centers were evaluated with a median follow-up of 38.3 months. The cumulative 1-, 2-, and 3-year incidences of locoregional recurrence were 5.6 %, 7.0 % and 13.1 % in the SBRT group versus 3.2 %, 4.8 % and 7.4 % in the surgery group, respectively [hazard ratio (HR), 1.97; 95 % confidence interval (CI), 0.74–5.24; P = 0.14]. The cancer-specific survival rates were 95.9 %, 94.5 % and 88.1 % versus 96.9 %, 94.6 % and 93.8 % in the SBRT and surgery groups respectively (HR, 1.72; 95 % CI, 0.67–4.44; P = 0.23). In the SBRT group, two patients (2.7 %) suffered from grade 3 radiation pneumonitis, while in the surgery group, grade 3 complications occurred in four (3.1 %) patients, and four cases were expired due to pneumonia or pulmonary heart disease within 90 days after surgery. Conclusions: SBRT is an effective therapeutic option with limited toxicity compared to surgery for patients with MPLCs after prior radical surgical resection, and it could be considered as an alternative treatment for those patients.